The Management of Parkinson's Disease: An Overview of the Current Advancements in Drug Delivery Systems - Deepa D. Nakmode; Candace M. Day; Yunmei Song; Sanjay Garg (MDPI AG, 2023)
Parkinson's disease (PD) has significantly affected a large proportion of the elderly population worldwide. According to the World Health Organization, approximately 8.5 million people worldwide are living with PD. In the United States, an estimated one million people are living with PD, with approximately 60,000 new cases diagnosed every year. Conventional therapies available for Parkinson's disease are associated with limitations such as the wearing-off effect, on-off period, episodes of motor freezing, and dyskinesia. In this review, a comprehensive overview of the latest advances in DDSs used to reduce the limitations of current therapies will be presented, and both their promising features and drawbacks will be discussed. We are also particularly interested in the technical properties, mechanism, and release patterns of incorporated drugs, as well as nanoscale delivery strategies to overcome the blood-brain barrier.